The Vaginal Microbiome: A Long Urogenital Colonization Throughout Woman Life - Auriemma, Renata S.; Scairati, Roberta; del Vecchio, Guendalina; Liccardi, Alessia; Verde, Nunzia; Pirchio, Rosa; Pivonello, Rosario; Ercolini, Danilo; Colao, Annamaria (Frontiers in Cellular and Infection Microbiology, 2021)
Vaginal microbial niche is a dynamic ecosystem, composed by more than 200 bacterial species which are influenced by genes, ethnic background and environmental-behavioral factors. Several lines of evidence have well documented that vaginal microbiome constantly changes over the course of woman’s life, so to exert an important impact on woman quality of life, from newborn to post-menopausal ages. This review aims at analyzing the role of vaginal microbiome in the maintenance of woman’s homeostasis and at tracking critical changes that commonly occur across woman’s lifetime. The role of hormone replacement therapy in the modulation of vaginal microbiome composition and in the improvement of vaginal wellness in postmenopausal women with decreasing levels of circulating estrogen is discussed.